Mobility based surveillance model to facilitate security of individuals’ properties - Hameed, Shihab A. (2013)
World Wide statistics show the increasing number of properties such as cars, house, and offices, in term of production and theft attempts. There is a big international effort in research and industrial production done to develop and produce security systems, but we still in need for more improvement since the number of theft cases are still increases. The thieves become more professional and inventing powerful stealing techniques which require more effective security systems. This research project tries to solve such problem by making use of the advancement in mobility and electronic technologies to develop an effective surveillance model. The proposed model integrates both Monitoring and Tracking activities and offers effective communication and controlling with owners, security units or police. It can send email to the owner on his mobile to have fast response especially if the car is nearby. Information about the property and the picture of the intruder will be sent to user, security unit or police. This will help police or security authorities in tracking property or car using GPS system that can be link to Google Earth and other mapping software. The implementation and testing results show the success of prototype in sending email to owner and receiving acknowledgment to the security unit or police within 3-4 minutes. The timing and results are suitable to owner, security unit, or police to take suitable action against intruder.